INDONESIA - FREEPORT ECONOMIC DISPUTE - Azaria, Farah Redina (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2020)
PT. Freeport Indonesia began operating in the Mimika district in Papua Province at the Gresberg mining. Their cooperation with Indonesia was marked with a contract of work I (Kontrak Karya / KK), with contract period of 30 years. The contract was made after the legalization of the investment LAW on 7 April 1967. This cooperation had been going long when KK II was established. However, in 2017 there was a change of regulation of natural resources management of Indonesia namely IUPK (Izin Usaha Pertambangan Khusus). This regulation initiated debate between Freeport and Indonesia government to reach a consensus. The method used to collect data in this study is qualitative method. Using mercantilist theory, this study suggests that state income and gains are major aspect in international cooperation. Keywords : Indonesia, Freeport, Mercantilism, and Foreign Policy